A critical review of biodegradable polymers for food packaging: Enhancing functionality and environmental sustainability - Ros Azlinawati, Ramli (Elsevier, 2026)
Biodegradable polymer-based food packaging has advanced rapidly in recent years, driven by the need to reduce reliance on conventional plastics while ensuring food safety, shelf-life extension, and environmental sustainability. This review examines the current state of biodegradable packaging through a focused analysis of material families, fabrication techniques, functional performance, and environmental life cycle considerations. It highlights recent progress in solution-based, thermomechanical, and electrospinning methods that enable tunable mechanical strength, gas - moisture barrier control, antimicrobial and intelligent sensing functionalities. Particular emphasis is placed on emerging strategies such as nanofiller reinforcement, green crosslinking chemistry, hybrid multilayer architectures, and real-time spoilage indicators. These approaches collectively narrow the performance gap with petroleum-based plastics. The review also synthesizes recent life cycle assessment findings, identifying key bottlenecks associated with processing energy demand, end-of-life variability, material contamination, and regulatory constraints. Together, these insights provide an updated perspective on technological trendsand persistent challenges. Uture directions are also needed to transition biodegradable polymers from experimental innovation to scalable, commercially viable, and environmentally responsible food packaging solutions.